Maize oleosin is correctly targeted to seed oil bodies in Brassica napus transformed with the maize oleosin gene. - Lee, W S (1991)
Oleosins are small hydrophobic abundant proteins localized in the oil bodies of plant seeds. An oleosin gene from the monocotyledonous maize (Zea mays L.) was transferred into the dicotyledonous Brassica napus L. using Agrobacterium-mediated transformation. The maize oleosin gene was placed under the control of either its own promoter/terminator or the promoter/terminator of a Brassica seed storage protein (napin) gene. Southern blot analyses of individual transformed plants suggested that the oleosin gene from either construct was incorporated into the Brassica chromosomes without appreciable structural alterations. The amount of construct incorporated was from 1 to >10 copies per haploid genome, depending on the individual transformant. Maize oleosin mRNA and protein were detected only in the transformants containing the napin gene promoter/terminator constructs; these transformants were studied further. Northern blot analyses of RNA isolated from different tissues and seeds of different developmental stages indicated that the maize oleosin mRNA was present only in the maturing seed. Approximately 1% of the total protein in mature seed was represented by maize oleosin. Subcellular fractionation of the mature seed revealed that 90% or more of the maize oleosin, as well as the Brassica oleosin, was localized in the oil bodies. The results show that a monocotyledonous oleosin possesses sufficient targeting information for its proper intracellular transport in a dicotyledon and also suggest that the napin gene promoter/terminator of Brassica, or equivalent seed storage protein regulatory elements of other plant species, may be used to express genes for the genetic engineering of seed oils.